Análise da percepção e do conhecimento espacial da criminalidade comparados ao registro oficial de ocorrências policiais - Luci Aparecida Nicolau (2011)
This dissertation investigates the correspondence between theindividual perceptions of the personal perception of criminality bymilitary policemen and the reality, considering a set of policereports on events of high social impact, such as disturbanceof the peace, illegal possession of weapons, use of drugs, drugstrafficking, burglary and theft. For that purpose, militarypolicemen from the city of Lavras (MG) answered to profilingquestionnaires and indicated on maps the regions in which theysupposed the highest concentrations of criminal events of each typewere taking place. These places were then compared to the actual setof criminal events, as recorded by the Military Police. Results showa remarkable difference between the personal perception andknowledge of the policemen and the actual distribution of events,and also show a considerable discrepancy among the perceptions ofthe policemen themselves. These discrepancies indicate that theroutine processing of police reports should include steps for thespatial analysis of the criminal behavior and the dissemination ofsuch information among the policemen, in order to increase theefficiency of the police actions through the strategic integrationof perceptions.